Substructures and Polypeptides of Visna Virus - Lin, Fu Hai (1974)
The protein of Visna virus, disrupted by 8 M guanidine hydrochloride and heating, was resolved into 10 polypeptides by agarose gel column chromatography in 6 M guanidine hydrochloride. Two of the peaks contained glycopolypeptides. Nonidet-disrupted virions were resolved into two fractions by potassium tartrate gradient centrifugation, with densities of 1.08 and 1.24 g/ml, respectively. About 70% of the viral DNA polymerase directed by added template was released into the light fraction, in which very little endogenous enzyme activity was detected. Also released into the light fraction were all of the glycopolypeptides, 50% of the viral RNA, and a part of each of the other viral protein components. The data indicate that extensive degradation of subviral structures occurred, even under mild conditions for virion disruption. The 1.24-g/ml fraction was composed of 50% of the viral RNA, most of the endogenous DNA polymerase activity (80%), and a major internal polypeptide (GuHCl6) with an estimated mol wt of 28,000. Two other polypeptides were also consistently detected in the heavy fraction, but they constituted less than 25% of the ribonucleoprotein complex, compared with 75% for GuHCl6.